Numerical study of active galactic nucleus feedback in an elliptical galaxy with MACER. Issue Volume 14:Issue S342(2018) (May 2018) - Yuan, Feng; Ostriker, Jeremiah P.; Yoon, DooSoo; Li, Ya-Ping; Ciotti, Luca; Gan, Zhao-Ming; Ho, Luis C.; Guo, Fulai
Abstract: This paper summarizes our recent works of studying AGN feedback in an isolated elliptical galaxy by performing high-resolution hydrodynamical numerical simulations. Bondi radius is resolved and the mass accretion rate of the black hole is calculated. The most updated AGN physics, namely the discrimination of cold and hot accretion modes and the exact descriptions of the AGN radiation and wind for a given accretion rate are adopted and their interaction with the gas in the host galaxy is calculated. Physical processes such as star formation and SNe feedback are taken into account. Consistent with observation, we find the AGN spends most of the time in the low-luminosity regime. AGN feedback overall suppresses the star formation; but depending on location in the galaxy and time, it can also enhance it. The light curve of specific star formation rate is not synchronous with the AGN light curve. These results put a serious challenge to the observational test of the relation between AGN activity and star formation. We find that wind usually plays a dominant role in controlling the AGN luminosity and star formation, but radiation also cannot be neglected.